A systematic review of effect of different welding process on mechanical properties of grade 5 titanium alloy. (2020) - Swapna Sai, M.; Dhinakaran, V.; Manoj Kumar, K.P.; Rajkumar, V.; Stalin, B.; Sathish, T.
Abstract: Welding is widely used in the final stage of the casting production and in fabricating the components for joining. The simplicity of titanium welding and its special effects on mechanical properties is therefore extremely important conditions in the case of engineering workings. The idea of this review is, to sum up the welding capability and its effects on mechanical properties of grade 5 titanium alloy tubes. It has been identified that the titanium welding is used in different fields throughout the world. The GTAW process is the best method to weld the titanium alloys.